Effective fracture zone under deep-hole cumulative blasting in coal seam - GUO De-yong; ZHAO Jie-chao; LÜ Peng-fei; ZHU Tong-gong (工程科学学报)
Deep-hole directional cumulative-blasting cracking technology has unique advantages for improving coal seam permeability. This paper was concerned with the range of the effective fracture zone under cumulative blasting using a linear-shaped charge in a coal seam. Based on the analysis of the mechanism of the directional cumulative-blasting in coal seams, the response characteristics of the coal under the coupled effects of the blasting-induced shock wave, stress wave, detonation gas and the energy-cumulative effect, and the partition characteristics of the crack in the cumulative-blasting-affected area were studied by theoretical analysis; moreover, a numerical analysis model of cumulative blasting was established, and the propagation distribution characteristics and range of coal seam fracture under cumulative blasting were investigated through numerical simulation. The results of the theoretical analysis and simulation show that the cumulative-blasting-affected area can be divided into crushed, crack, and elastic-deformation zones; further, the crack zone can be divided into crack-intensive and main crack-propagation zones according to the type and number of cracks. Additionally, a partition model for the influence of deep-hole cumulative blasting with linear-shaped charge in coal seams was constructed. Meanwhile, under the influence of the shaped-charge structure, the crushed zone has an oval-like shape with a small radius in the direction of the shaped-charge jet, while the crack-intensive and main crack-propagation zones have oval-like shapes with a larger radius in the direction of the shaped-charge jet. In addition, field experiments of deep-hole cumulative blasting with linear-shaped charge in coal seams were carried out and the experimental results show that the influence of the cumulative blasting on the increase of the coal-seam-gas volume fraction in each observation hole weakened in a step-wise manner (strong-medium-weak) with increasing distance from the blasting borehole; this is consistent with the partition model of the constructed cumulative blasting, i.e., the cumulative-blasting-affected area has certain zoning characteristics, and the crushed, crack-intensive, and main crack-propagation zones are the main components of the effective fracture zone.